PENGARUH PERMAINAN KARTU EMOSI TERHADAP KEMAMPUAN SOSIOEMOSIONAL MASA KANAK-KANAK AWAL DI TAMAN KANAK-KANAK KOTA MALANG - Siti Fatimah (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2022)
The purpose of this writing is to determine whether there is an influence of emotional card games on early childhood socio-emotional abilities in kindergartens in Malang. This study uses a design with a quantitative approach. The type of research to be used is experimental research where experimental research can be interpreted as a research method used to find the effect of certain treatments on others under controlled conditions. The type of experimental research design that will be used is experimental randomized two group design posttest only. The research population in this experiment were students of TK ABA Aisyiah, TK NU 16 Malang, and TK NU 27 Malang. The sampling method used by the authors is the non-probability sample design. After that do randomization. The samples in this study were 10 students of TK ABA Aisyiah, 10 students of TK NU 16 Malang, and 10 students of TK NU 27 Malang. Samples were taken randomly recommended by the kindergarten teacher concerned. Data collection was carried out by making observation guidelines in the form of checklists that were used during the pre-test and post-test. From these results, data will be obtained that are used as a basis for testing the research hypothesis, namely the hypothesis is accepted or rejected. To find out whether providing information about emotions has an effect on social-emotional abilities in early childhood in the city of Malang, uncorrelated data/independent sample t-test is calculated. Based on the results of the research and discussion above, it can be seen that there is no effect of emotional card games on the development of socio-emotional abilities and TOM in early childhood in Malang City Kindergarten after manipulation of instructions. This shows that there is no significant increase in the ability to manipulate the behavior of students in Kindergarten in Malang city.